Rainbow trapping in a chirped three-dimensional photonic crystal - Zeki Hayran (Nature Portfolio, 2017)
Abstract Light localization and intensity enhancement in a woodpile layer-by-layer photonic crystal, whose interlayer distance along the light propagation direction is gradually varied, has been theoretically predicted and experimentally demonstrated. The phenomenon is shown to be related to the progressive slowing down and stopping of the incident wave, as a result of the gradual variation of the local dispersion. The light localization is chromatically resolved, since every frequency component is stopped and reflected back at different positions along the crystal. It has been further discussed that the peculiar relation between the stopping position and the wave vector distribution can substantially increase the enhancement factor to more than two orders of magnitude. Compared to previously reported one- and two-dimensional photonic crystal configurations, the proposed scheme has the advantage of reducing the propagation losses by providing a three-dimensional photonic bandgap confinement in all directions. The slowing down and localization of waves inside photonic media can be exploited in optics and generally in wave dynamics, in many applications that require enhanced interaction of light and matter.